Seismic Soil-structure Interaction: A State-of-the-Art Review. (November 2018) - Anand, Vishwajit; Satish Kumar, S.R.
Abstract: The process of soil response influencing motion of the structure and vice-versa is termed as soil-structure interaction (SSI). SSI has been traditionally considered to be beneficial to seismic response of a structure. It has been suggested that ignoring SSI in design practice leads to a conservative design. It is evident from the design codes which either allow a reduction of the overall seismic coefficient on account of SSI or suggest it to be ignored altogether. However observations from some of the past seismic events such as 1989 Loma Prieta earthquake and 1995 Kobe Earthquake show evidences of detrimental nature of SSI in certain circumstances. Recent studies have also been able to justify such possibilities. As a consequence of this dissent among the research fraternity, there is a lack of adequately formulated design guidelines. Though advances have been made in developing methods to solve an SSI problem, incorporating SSI in design practice has been a rarity. The present paper attempts to summarize various approaches to include SSI in analysis of structures and guidelines outlined in prominent seismic codes. The significance of such a study lies in the need for selection of appropriate approach. A review of contemporary research in field of SSI is also presented at the end. Highlights: Significance of soil-structure interaction (SSI) in seismic design is established. Various approaches to solve an SSI problem are explained. SSI provisions in prominent seismic codes are discussed. Contemporary research in field of SSI is reviewed.